PRESERVASI KAWASAN PERDAGANGAN KOTAGEDE YOGYAKARTA DENGAN PENDEKATAN ADAPTIVE REUSE - Yetti, Aprodita Emma (Jurnal Arsitektur dan Perencanaan (JUARA), 2018)
Abstract: Pasar Gede Kotagede had a role as the center of the economy since the Islamic Mataram empire stands. Pasar Gede and surroundings has an attraction for people and travelers to come and stay in Kotagede. Cultural acculturation not only show up from the social side but also appears in the architectural. However, the development of the era and the residents as slowly erode the architectural form in the buildings and the area around Pasar Gede. This research uses qualitative explorative method to study the theory with "adaptive reuse" approach and explore the findings in site. The results of this research aims to produce preservation policy, to maintain the activities of economic and trading activities that have been very solid and environmental improvements to be more responsive and more 'wise' in visual perspective on architectural physical to improve the smoothness of activities and comfort.Keywords: Preservation, Adaptive Reuse, Pasar Gede